Surface-enhanced Raman spectroscopy of blood plasma and serum using Ag and Au nanoparticles: a systematic study - Bonifacio, Alois; Dalla Marta, Silvia; Spizzo, Riccardo; Cervo, Silvia; Steffan, Agostino; Colombatti, Alfonso; Sergo, Valter (Analytical and bioanalytical chemistry, 2014)
Surface-enhanced Raman spectroscopy (SERS) is a good candidate for the development of fast and easy-to-use diagnostic tools, possibly used on biofluids in point-of-care or screening tests. In particular, label-free SERS spectra of blood serum and plasma, two biofluids widely used in diagnostics, could be used as a metabolic fingerprinting approach for biomarker discovery. This study aims at a systematic evaluation of SERS spectra of blood serum and plasma, using various Ag and Au aqueous colloids, as SERS substrates, in combination with three excitation lasers of different wavelengths, ranging from the visible to the near-infrared. The analysis of the SERS spectra collected from 20 healthy subjects under a variety of experimental conditions revealed that intense and repeatable spectra are quickly obtained only if proteins are filtered out from samples, and an excitation in the near-infrared is used in combination with Ag colloids. Moreover, common plasma anticoagulants such as EDTA and citrate are found to interfere with SERS spectra; accordingly, filtered serum or heparin plasma are the samples of choice, having identical SERS spectra. Most bands observed in SERS spectra of these biofluids are assigned to uric acid, a metabolite whose blood concentration depends on factors such as sex, age, therapeutic treatments, and various pathological conditions, suggesting that, even when the right experimental conditions are chosen, great care must be taken in designing studies with the purpose of developing diagnostic tests.